IMF Research Bulletin, March 2012. (IMF Research Bulletin; IMF Research Bulletin ;, 2012)
The research summaries in the March 2012 issue of the IMF Research Bulletin are "Foreign Direct Investment and the Crisis: Is This Time Different?" (by Yuko Kinoshita) and "Food Prices and Inflation" (by James P. Walsh). The Q and A covers seven questions on "Unemployment through the Prism of the Great Recession" (by Prakash Loungani). This issue also launches a new feature "Conversations with Visiting Scholars" with an interview with Tom Sargent, winner of the 2011 Nobel Prize in Economic Sciences. Also included in this issue are details on visiting scholars at the IMF, a listing of recently published IMF Working Papers, and information on the next issue of "IMF Economic Review.".